The West Kunlun Glacier Anomaly and Its Response to Climate Forcing during 2002–2020 - Luo, Jianwei; Ke, Chang-Qing; Seehaus, Thorsten (Remote Sensing, 2022)
Research into glacial mass change in West Kunlun (WK) has been sufficient, but most of the existing studies were based on geodetic methods, which are not suitable for specific health state analyses of each glacier. In this paper, we utilize Advanced Spaceborne Thermal Emission and Reflection Radiometer (ASTER) imagery, applying the continuity equation to obtain altitudinal specific mass balance (SMB) for 615 glaciers (>2 km2) during 2002–2011, 2011–2020, and 2002–2020 to research glacial health and its response to climatic forcing. The results show dissimilar glacier SMB patterns between 2002–2011 (0.10 ± 0.14 m w.e. a−1), 2011–2020 (–0.12 ± 0.14 m w.e. a−1) and 2002–2020 (−0.01 ± 0.07 m w.e. a−1). Additionally, the glacier equilibrium line altitude (ELA) in WK was 5788 m, 5744 m, and 5786 m, respectively, and the corresponding accumulation area ratios (AARs) were 0.59, 0.62, and 0.58, during 2002–2011, 2011–2020, and 2002–2020, respectively. Regarding glacier response, compared with the ordinary-least-square (OLS) model, the artificial neural network (ANN) model revealed a respectively less and more sensitive glacier SMB response to extreme negative and positive summer skin temperatures. In addition, the ANN model indicated that the glacier ELA was less sensitive when the integrated water vapor transport (IVT) change exceeded 0.7 kg m−1s−1. Moreover, compared with IVT (−121.57 m/kg m−1s−1), glacier ELA shifts were chiefly dominated by summer skin temperature (+154.66 m/℃) in the last two decades. From 2002–2011 and 2011–2020, glacier SMB was more susceptible to summer skin temperature (−0.38 m w.e./℃ and −0.16 m w.e./℃, respectively), while during 2002–2020, it was more influenced by IVT (0.45 m w.e./kg m−1s−1). In contrast with eastern WK, glaciers in western WK were healthier, although mitigation measures are still needed to safeguard glacier health and prevent possible natural hazards in this region. Finally, we believe that the inconsistent change between glacier SMB and ELAs from 2002–2020 was connected with ice rheology and that the combined effects of skin temperature and IVT can explain the WK glacier anomaly.<br
Keywords: specific mass balance; continuity equation; glacier health; glacier response; West Kunlun